Linear and Nonlinear Interactions in Hybrid Microresonators with Controllable Coupling - Pal, Arghadeep; Ghosh, Alekhya; Zhang, Hao; Ghalanos, George; Bi, Toby; Zhang, Shuangyou; Hill, Lewis; Del'Haye, Pascal (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We investigate linear and nonlinear dynamics of light in coupled resonators. In our experiments, we can adjust the coupling gap between two resonators in real-time to study symmetry breaking of hybridized counterpropagating modes.
CRIS-Team Scopus Importer:2024-10-04